Optimasi Sistem Panel Surya dan Baterai Untuk Meminimasi Biaya Pemakaian Energi Listrik Rumah Tangga - Zebua, Osea; Ginarsa, I Made (DIELEKTRIKA, 2024)
The use of photovoltaic-battery energy storage systems to meet the electrical energy needs of house while reducing the cost of using electricity from the grid is increasing. Optimization of this system can be performed by optimizing the energy consumption of solar panels and batteries. This paper presents the optimization of solar panels and battery systems to minimize the cost of using electricity from the grid. Circuit models and mathematical formulations of grid-connected solar panel and battery systems were created for optimization purposes. The optimization problem is solved by using mixed-integer linear programming and Pyomo software based on the Python programming language. Data on household electricity consumption and output power from two solar panels with a capacity of 100 Wp and 200 Wp respectively were obtained from the results of simultaneous measurements for one month. The test results show that the optimization of the solar panel and battery system can reduce the cost of electricity consumption at home with optimal energy consumption from solar panels and batteries.